A flexible stone veneer manufacturing process

CN123001237APending Publication Date: 2026-10-30JIANGSU EVERGREEN DECORATING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611377030.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]针对现有技术的不足,本发明提供了一种柔性石材饰面加工工艺,解决了单一树脂体系固化产生高收缩内应力导致板材翘曲变形,以及多组分树脂共混体系室温操作期短、固化反应进度不可控且各层界面间化学附着力差的问题

Benefits of technology

1、本发明通过引入温度响应型螯合催化开关络合物与甲乙酮肟封闭型聚氨酯预聚体,构建双阶段固化体系,在常温及第一阶段固化环境中,催化剂内锡金属中心受配体稳定螯合而处于催化惰性状态,预聚体端基维持封闭状态,此时体系内仅发生聚醚胺与环氧基团的缓和开环加成反应,双阶段分离机制将环氧交联反应与聚氨酯接枝反应解耦为独立过程,有助于规避多组分体系在同一时段内剧烈反应引发的内应力聚集现象,并且延长反应型复合胶液的室温操作窗口,有利于提升加工作业的容错率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123001237A_ABST
    Figure CN123001237A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of stone facing processing, and discloses a flexible stone facing processing technology, which comprises the following steps: mixing 4,4'- (1-methylethylene) bisphenol and a polymer of (chloromethyl) oxirane, resorcinol tetraphenyl diphosphate and aluminum hydroxide; adding methyl ethyl ketone oxime blocked polyurethane prepolymer, polyether amine and a temperature-responsive chelating catalytic switch complex to prepare a reactive composite glue solution; applying the reactive composite glue solution to the back of natural stone, laying a glass fiber mesh cloth layer and a glass steel layer and applying a pressing pressure; through first-stage curing, an epoxy group is crosslinked with polyether amine to form a bottom layer skeleton and generate a secondary hydroxyl group; in the second stage, temperature rising triggers the temperature-responsive chelating catalytic switch complex to release a catalytic center, so that the prepolymer is unblocked, and the released isocyanate group is grafted and crosslinked with the secondary hydroxyl group. The present application utilizes a two-stage curing mechanism, which is helpful to reduce the internal stress of the matrix and improve the adhesion of the plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of stone surface processing technology, specifically a flexible stone surface processing technology. Background Technology

[0002] As architectural decoration moves towards lightweight and curved surfaces, the application of traditional natural stone is limited in irregular and curved wall surfaces due to its thickness, weight, and limited bending performance. Existing technologies are gradually adopting ultra-thin natural stone combined with supporting materials such as fiberglass mesh and fiberglass to balance the texture, lightweight, and certain bending performance of natural stone.

[0003] In the composite processing, resin-based adhesives are usually used to press and bond the natural stone surface layer with the reinforcing and supporting layers. Existing single resin systems generate large shrinkage internal stress during curing, which leads to warping and deformation of the slab. Although some multi-component resin systems can improve flexibility, the room temperature operating period after mixing is short, and multiple reactive groups cure at the same time, making the reaction process difficult to control. This affects the wetting of each structural layer and the interfacial bonding of the adhesive, resulting in insufficient interlayer adhesion and overall structural stability. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a flexible stone veneer processing technology that solves the problems of high shrinkage internal stress caused by curing of single resin systems leading to warping and deformation of the slabs, as well as the problems of short room temperature operation time, uncontrollable curing reaction progress, and poor chemical adhesion between interfaces of multi-component resin blend systems.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A flexible stone veneer processing technology includes the following steps: The polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, resorcinol tetraphenyl diphosphate, and aluminum hydroxide were mixed and stirred to obtain a base mixture; Methyl ethyl ketone oxime blocked polyurethane prepolymer, polyetheramine and temperature-responsive chelating catalytic switching complex are added to the base mixture, and after degassing and stirring, a reactive composite adhesive is finally obtained. Prepare a natural stone surface layer, and evenly apply the reactive composite adhesive to the back of the natural stone surface layer; then lay a fiberglass mesh layer on the surface of the reactive composite adhesive, and roll it to make the reactive composite adhesive completely penetrate the fiberglass mesh layer; then cover the surface of the fiberglass mesh layer with a fiberglass layer, and send the laminated board into a hot press to apply pressure. The first stage of curing is carried out by heating and holding under pressure, which promotes the initial cross-linking of epoxy groups in the mixture with polyetheramine to form the underlying framework and generates secondary hydroxyl groups; The second stage of curing is carried out by continuing to heat up and maintaining constant temperature and pressure. The temperature-responsive chelate catalytic switching complex releases free tin metal centers in response to heat changes. Under the catalysis of the free tin metal centers, the methyl ethyl ketone oxime-blocked polyurethane prepolymer is deblocked and releases isocyanate. This causes the isocyanate to graft crosslink with the secondary hydroxyl groups generated in the first stage. After natural cooling, a flexible stone finish is obtained.

[0006] By adopting the technical solution of this invention, the epoxy ring-opening crosslinking and polyurethane desealing grafting are separated into independent processes due to the use of a two-stage curing system combined with a temperature-responsive catalytic mechanism. Therefore, the effects of extending the working period of the adhesive and reducing the internal stress of the board during curing and improving the interfacial adhesion are achieved. Specifically, in the first stage of curing, the polyetheramine in the system undergoes an epoxy-amine ring-opening addition reaction with the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide. The primary amine at the end of the polyetheramine attacks the epoxy group to form a macromolecular three-dimensional crosslinked underlying framework. This framework structure provides the basis for the shaping of the main body size. At the same time, the ring-opening reaction is accompanied by the generation of a large number of secondary hydroxyl groups.

[0007] In this environmental stage, the tin metal center in the temperature-responsive chelating catalytic switching complex is stably chelated by the ligand and is in a catalytically inert state. The methyl ethyl ketone oxime-blocked polyurethane prepolymer has not reached the deblocking condition and maintains its own chemical stability. The crosslinking process of the underlying skeleton is relatively mild, which helps to avoid the accumulation of interfacial stress caused by rapid exothermic reaction.

[0008] As the process progresses to the second stage of curing, the temperature-responsive chelate catalytic switching complex undergoes thermodynamic dissociation due to heat transfer, ligands detach, and highly catalytically active free tin metal centers are released. Under the catalysis of these free tin metal centers, the deblocking activation energy of the methyl ethyl ketone oxime-blocked polyurethane prepolymer decreases, the methyl ethyl ketone oxime leaves, and the prepolymer end groups release highly active isocyanate groups. The free isocyanate groups undergo in-situ grafting and crosslinking reactions with the secondary hydroxyl groups generated in the first stage to form urethane bonds. This grafting and crosslinking action introduces flexible polyurethane segments into the rigid epoxy underlayer skeleton through covalent bonds, forming an interpenetrating network structure. This mechanism is beneficial for improving the elongation at break and impact resistance of stone veneers.

[0009] Preferably, the step of mixing and stirring the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, resorcinol tetraphenyl diphosphate, and aluminum hydroxide to obtain the base mixture includes: 90 to 110 parts by weight of the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, 12 to 18 parts by weight of resorcinol tetraphenyl diphosphate, and 20 to 30 parts by weight of aluminum hydroxide are added to a high-speed disperser, the speed is set to 1000 to 1500 r / min and the mixture is stirred continuously for 14 to 20 min to obtain the base mixture.

[0010] By adopting this preferred technical solution, controlling the weight ratio and dispersion conditions of the polymer, flame retardant plasticizer and inorganic filler is beneficial to promoting the uniform dispersion of resorcinol tetraphenyl diphosphate and aluminum hydroxide in the resin matrix. Resorcinol tetraphenyl diphosphate has the effects of flame retardancy and reducing the viscosity of the system. Combined with high-speed shearing, it helps to break the agglomeration state between aluminum hydroxide particles and improve the homogeneity of the base material.

[0011] Preferably, the step of adding methyl ethyl ketone oxime-blocked polyurethane prepolymer, polyetheramine, and temperature-responsive chelating catalytic switching complex to the base mixture, followed by degassing and stirring, to finally obtain a reactive composite adhesive includes: After adding 15 to 25 parts by weight of methyl ethyl ketone oxime-blocked polyurethane prepolymer, 30 to 40 parts by weight of polyetheramine, and 1.2 to 1.8 parts by weight of temperature-responsive chelating catalytic switching complex to the base mixture, the planetary mixer is started and the speed is set to 350 r / min to 450 r / min. The mixture is continuously degassed and stirred for 8 to 12 minutes under a vacuum of -0.085 MPa to -0.095 MPa to finally obtain a reactive composite adhesive.

[0012] By adopting this preferred technical solution, the amount of curing system and catalyst introduced is clearly defined. 30 to 40 parts by weight of polyetheramine provides sufficient active hydrogen for the epoxy groups to maintain the conversion rate of the first-stage ring-opening reaction. 1.2 to 1.8 parts by weight of temperature-responsive chelating catalytic switching complex provides the free tin concentration required for the subsequent desealing reaction. Degassing and stirring are carried out under negative pressure to facilitate the removal of air mixed in during mixing and reduce the risk of microbubbles expanding during the hot-press curing stage and causing void defects at the adhesive layer interface.

[0013] Preferably, the step of preparing the natural stone surface layer and uniformly applying the reactive composite adhesive to the back of the natural stone surface layer includes: Prepare a natural stone surface layer with a thickness of 3.0 mm to 5.0 mm, and control the coating amount of the reactive composite adhesive to be 750 g / m². 2 Up to 850g / m 2 Apply the ointment; The step of laying a fiberglass mesh layer on the surface of the reactive composite adhesive includes: The mass per unit area of ​​the reactive composite adhesive liquid is 150 g / m². 2 Up to 170g / m 2 Fiberglass mesh layer; The steps of covering the surface of the fiberglass mesh layer with a fiberglass reinforced plastic (FRP) layer and then feeding the laminated sheet into a hot press to apply pressing pressure include: A fiberglass layer with a thickness of 0.8 mm to 1.2 mm is covered on the surface of the fiberglass mesh, and the laminated plate is sent into a hot press with a pressing pressure of 0.6 MPa to 0.9 MPa.

[0014] By adopting this preferred technical solution, the specifications and operating conditions of each physical composite layer are limited, and the amount of adhesive applied is matched with the unit area mass of the fiberglass mesh layer. This promotes the deep penetration of the reactive composite adhesive into the warp and weft gaps of the mesh under pressure, achieving dense filling of the interface between the natural stone, the mesh, and the fiberglass layer, which has a positive impact on improving the interlayer shear strength of the overall structure.

[0015] Preferably, the step of heating and holding under pressure to perform the first stage of curing, which promotes the initial cross-linking of the epoxy groups in the mixture with the polyetheramine to form the underlying framework and generates secondary hydroxyl groups, includes: After being kept at a constant temperature and pressure of 35℃ to 45℃ for 1.5h to 2.5h, and after titration to confirm that the primary amine conversion rate in the system is greater than 97.6%, the epoxy groups in the mixture are initially cross-linked with the polyether amine to form the underlying framework, and secondary hydroxyl groups are generated.

[0016] By adopting this preferred technical solution, the ambient temperature of the first stage is controlled within the range of 35℃ to 45℃. The controlled ambient temperature meets the requirements of the ring-opening crosslinking kinetics of epoxy groups and polyetheramine, and is much lower than the unblocking trigger temperature of closed polyurethane. Setting a chemical control node with a primary amine conversion rate greater than 97.6% is beneficial to the basic formation of the underlying skeleton structure and accumulates sufficient secondary hydroxyl attachment points for the second stage reaction, reducing the overlap and interference between the two stages of reaction.

[0017] Preferably, before the step of adding methyl ethyl ketone oxime-blocked polyurethane prepolymer, polyetheramine, and temperature-responsive chelating catalytic switching complex to the base mixture, and then degassing and stirring to finally obtain the reactive composite adhesive, the step of preparing the methyl ethyl ketone oxime-blocked polyurethane prepolymer includes: Poly(tetrahydrofuran) was dehydrated under vacuum and then cooled for later use. While maintaining a nitrogen protective atmosphere, isoflurone diisocyanate was added, followed by heating and stirring at a constant temperature to obtain NCO-terminated polyurethane prepolymer. After cooling, methyl ethyl ketone oxime was added dropwise at a uniform rate, and the reaction was carried out in a closed environment at a constant temperature to obtain a methyl ethyl ketone oxime-blocked polyurethane prepolymer.

[0018] By adopting this preferred technical solution, a closed prepolymer with a specific chain segment structure is synthesized. The main chain of the prepolymer is established by polymerization of isoflurane diisocyanate. The alicyclic structure provides weather resistance, and the poly(tetrahydrofuran) segment gives the polyurethane component low-temperature flexibility. Methyl ethyl ketone oxime is used to block the terminal isocyanate group, thereby temporarily inhibiting the reactivity of the terminal isocyanate group at room temperature.

[0019] Preferably, the step of dehydrating the poly(tetrahydrofuran) under vacuum conditions and then cooling it for later use includes: 95 to 105 parts by weight of poly(tetrahydrofuran) were subjected to a dehydration reaction at 105°C to 115°C and a vacuum of -0.085 MPa to -0.095 MPa for 1.5 to 2.5 hours, and then cooled for later use. The steps of maintaining a nitrogen protective atmosphere, adding isoflurane diisocyanate, and then heating and stirring at a constant temperature to obtain the NCO-terminated polyurethane prepolymer include: Maintaining a nitrogen protective atmosphere, add 38.0 to 51.3 parts by weight of isophorone diisocyanate, controlling the molar ratio of NCO groups in the isophorone diisocyanate to OH groups in the poly(tetrahydrofuran) to be 1.8 to 2.2, then raise the temperature to 75°C to 82°C, and stir the reaction at a constant temperature for 2.0 h to 3.0 h to obtain an NCO-terminated polyurethane prepolymer; The steps of uniformly adding methyl ethyl ketone oxime after cooling and reacting in a sealed environment at a constant temperature to obtain the methyl ethyl ketone oxime-blocked polyurethane prepolymer include: The temperature was lowered to 48°C to 52°C, and 13.9 to 24.2 parts by weight of methyl ethyl ketone oxime were added dropwise at a uniform rate, keeping the internal temperature below 62°C. After the addition was complete, the mixture was kept at a constant temperature of 58°C to 62°C and sealed for 1.5 to 2.5 hours to obtain a methyl ethyl ketone oxime-blocked polyurethane prepolymer.

[0020] By adopting this preferred technical solution, the polymerization control parameters of the polyurethane prepolymer are strictly quantified, and vacuum dehydration treatment is used to eliminate moisture interference and prevent water molecules from consuming isocyanate to produce carbon dioxide byproducts. The molar ratio of NCO to OH groups is controlled to be 1.8 to 2.2, which is conducive to end-capping the prepolymer with isocyanate groups. The internal temperature during the addition of methyl ethyl ketone oxime is limited to below 62°C, which helps to avoid the phenomenon of self-polymerization or local boiling caused by violent exothermic reaction and maintain a good end-capping conversion rate.

[0021] Preferably, before the step of adding methyl ethyl ketone oxime-blocked polyurethane prepolymer, polyetheramine, and temperature-responsive chelating catalytic switching complex to the base mixture, followed by degassing and stirring to finally obtain the reactive composite adhesive, the step of preparing the temperature-responsive chelating catalytic switching complex includes: In a dry environment, dibutyltin dilaurate and acetylacetone are mixed and continuously stirred magnetically; By using acetylacetone as both a reaction solvent and a carrier, a coordination chelation reaction is initiated between the enol hydroxyl groups in acetylacetone and the tin metal center, thus obtaining a temperature-responsive chelate catalytic switching complex.

[0022] By adopting this preferred technical solution, acetylacetone is used as both a ligand and a solvent medium to coordinate the central tin atom in dibutyltin dilaurate with the enol structure of acetylacetone. The coordination reaction changes the steric hindrance distribution of the tin atom, inhibits the catalytic activity of the central tin atom at room temperature, and achieves the purpose of catalyst dormancy at room temperature.

[0023] Preferably, the step of mixing dibutyltin dilaurate with acetylacetone and continuously stirring magnetically in a dry environment includes: In a dry environment at 22°C to 28°C, dibutyltin dilaurate and acetylacetone were added to a mixing container at a mass ratio of 1:6-10, and the stirring speed was set to 300 r / min to 400 r / min. The mixture was then continuously stirred magnetically for 15 min to 30 min.

[0024] By adopting this preferred technical solution, a mass ratio of 1:6-10 is set to enable acetylacetone to provide an excess of coordinating groups and a sufficient liquid solvent environment, thereby shifting the coordination reaction equilibrium to the forward direction. By coordinating the rotation speed and time, the probability of intermolecular collisions is increased, thereby improving the yield and stability of the chelate.

[0025] Preferably, the step of continuing to heat and maintain constant temperature and pressure for the second stage of curing, wherein the temperature-responsive chelate catalytic switching complex releases free tin metal centers in response to heat changes, and under the catalysis of the free tin metal centers, triggers the deblocking of the methyl ethyl ketone oxime-blocked polyurethane prepolymer and the release of isocyanate ions, includes: The temperature of the hot press is raised to 75°C to 85°C and held at a constant temperature for 2.5h to 4.0h. The temperature-responsive chelating catalytic switching complex releases free tin metal centers in response to heat changes. When the system reaches 72°C to 78°C, the methyl ethyl ketone oxime-blocked polyurethane prepolymer is triggered to deblock and release isocyanate.

[0026] By adopting this preferred technical solution, a second-stage thermodynamic control range is set. The processing temperature of 75°C to 85°C provides sufficient heat energy to break the acetylacetone-tin coordination bond. The system reaches 72°C to 78°C as the desealing trigger condition, which is conducive to the orderly release of isocyanate and its capture and cross-linking by the high concentration of secondary hydroxyl groups in the system. The specific temperature setting shortens the residence time of free isocyanate and restricts the migration of isocyanate to the outside, further improving the chemical stability and interlayer peel strength of the final flexible stone surface.

[0027] This invention provides a flexible stone veneer processing technology. It has the following beneficial effects: 1. This invention constructs a two-stage curing system by introducing a temperature-responsive chelating catalytic switching complex and a methyl ethyl ketone oxime-blocked polyurethane prepolymer. In the room temperature and first-stage curing environment, the tin metal center in the catalyst is stably chelated by the ligand and is in a catalytically inert state, while the end groups of the prepolymer remain blocked. At this time, only the mild ring-opening addition reaction between polyetheramine and epoxy groups occurs in the system. The two-stage separation mechanism decouples the epoxy crosslinking reaction and the polyurethane grafting reaction into independent processes, which helps to avoid the internal stress accumulation phenomenon caused by the violent reaction of multi-component systems in the same period of time, and extends the room temperature operating window of the reactive composite adhesive, which is beneficial to improving the error tolerance of the processing operation.

[0028] 2. This invention utilizes the large number of secondary hydroxyl groups generated during the first-stage curing reaction as subsequent grafting sites. Combined with the thermodynamic heating triggering mechanism of the second stage, it promotes in-situ crosslinking of the isocyanate groups released from the prepolymer with the secondary hydroxyl groups. The in-situ grafting action introduces flexible polyurethane segments into the rigid epoxy substrate skeleton through covalent bonding, constructing an interpenetrating network structure with microphase separation characteristics. This specific network structure has good stress dissipation capabilities, which helps reduce the structural deformation caused by the curing shrinkage of the resin matrix. At the same time, it increases the chemical adhesion between the natural stone and the support layer, playing a positive role in improving the fracture resistance and impact resistance of the stone surface.

[0029] 3. This invention incorporates resorcinol tetraphenyl diphosphate and aluminum hydroxide during the base mixture preparation stage. The flame-retardant plasticizing components reduce the viscosity of the resin matrix and promote the uniform dispersion of inorganic fillers. Combined with the pressing pressure applied by the hot press, the reactive composite adhesive deeply penetrates the warp and weft gaps of the fiberglass mesh layer. The physical lamination process and chemical grafting crosslinking work together to establish a dense filling state between the natural stone surface layer, the fiberglass mesh layer, and the fiberglass layer. This helps to improve the overall interlayer shear strength of the composite board and provides flame-retardant protection and physical shaping support for the final finished surface material. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the viscosity evolution curve of the system under isothermal conditions according to the present invention; Figure 2 This is a schematic diagram of the microphase evolution trajectory of the solidified product according to the present invention; Figure 3 This is a schematic diagram of the decay curve of the mass percentage of the present invention as a function of heating temperature; Figure 4 This is a schematic diagram of the thermal weight loss rate as a function of heating temperature according to the present invention. Figure 5This is a schematic diagram showing the evolution curves of peeling displacement and peeling load strength according to the present invention. Figure 6 This is a schematic diagram of the curve showing the relative interface residual cohesion retention rate as a function of bending curvature according to the present invention. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0033] A polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, CAS No. 25068-38-6, with an epoxy equivalent of 210 to 240 g / eq; Poly(tetrahydrofuran), CAS No. 25190-06-1, number average molecular weight is 1000 g / mol, hydroxyl value is 110 to 115 mg KOH / g; Polyetheramine, CAS No. 9046-10-0, is limited to amino-terminated polyoxypropylene ether with an average molecular weight of 400 g / mol and a total amine value of 4.3 to 4.6 meq / g; Resorcinol tetraphenyl diphosphate, CAS No. 57583-54-7, has a phosphorus mass fraction of 10.7% to 10.9% and is a liquid with a viscosity of 400 to 600 mPa·s at room temperature; Aluminum hydroxide, CAS No. 21645-51-2, is an inorganic powder with surface modified by γ-aminopropyltriethoxysilane coupling agent, and an average particle size D50 of 1.0 to 2.0 μm; The natural stone surface layer is made of granite and is 3.0 to 5.0 mm thick; The unit area mass of the fiberglass mesh layer is 150g / m². 2 Up to 170g / m 2 ; The fiberglass layer is an epoxy resin-based continuous unidirectional fiberglass pultruded sheet with a thickness of 0.8mm to 1.2mm and a fiberglass mass fraction of 60% to 65%.

[0034] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.

[0035] Preparation Example 1: This preparation example provides a method for preparing a methyl ethyl ketone oxime-blocked polyurethane prepolymer, including the following steps: 100 parts by weight of poly(tetrahydrofuran) were added to a three-necked flask and the dehydration reaction was carried out at 110°C and a vacuum of -0.09 MPa for 2.0 h. Then the internal temperature of the three-necked flask was reduced to 40°C for later use. Maintaining a nitrogen protective atmosphere, 44.5 parts by weight of isoflurane diisocyanate were added to a three-necked flask, controlling the molar ratio of NCO groups to OH groups in the added substance to be 2.0. Then, the internal temperature of the three-necked flask was raised to 78°C, and the reaction was stirred at a constant temperature for 2.5 h. The mass fraction of free NCO groups in the mixture in the three-necked flask was measured to be 5.8%, and NCO-terminated polyurethane prepolymer was obtained. The internal temperature of the three-necked flask was lowered to 50°C, and 18.3 parts by weight of methyl ethyl ketone oxime was added dropwise at a uniform rate. The dropping rate was controlled, and the internal temperature of the three-necked flask was kept below 60°C. After the addition was complete, the mixture was kept at a constant temperature of 60°C in a sealed container for 2.0 hours. The reaction time was confirmed by infrared spectroscopy at 2270 cm⁻¹. -1 The characteristic absorption peak of NCO completely disappeared, and the methyl ethyl ketone oxime blocked polyurethane prepolymer was finally obtained, hereinafter referred to as blocked prepolymer A.

[0036] Preparation Example 2: This preparation example provides a method for preparing a methyl ethyl ketone oxime-blocked polyurethane prepolymer, including the following steps: 95 parts by weight of poly(tetrahydrofuran) were added to a three-necked flask and the dehydration reaction was carried out at 105°C and a vacuum of -0.085 MPa for 1.5 h. Then the internal temperature of the three-necked flask was reduced to 38°C for later use. Maintaining a nitrogen protective atmosphere, 38.0 parts by weight of isoflurane diisocyanate were added to a three-necked flask, controlling the molar ratio of NCO groups to OH groups in the added substance to be 1.8. Then, the internal temperature of the three-necked flask was raised to 75°C, and the reaction was stirred at a constant temperature for 2.0 h. The mass fraction of free NCO groups in the mixture in the three-necked flask was measured to be 4.8%, and NCO-terminated polyurethane prepolymer was obtained. The internal temperature of the three-necked flask was lowered to 48°C, and 13.9 parts by weight of methyl ethyl ketone oxime was added dropwise at a uniform rate. The dropping rate was controlled, and the internal temperature of the three-necked flask was kept below 58°C. After the addition was complete, the flask was kept at a constant temperature of 58°C and sealed for 1.5 hours. The reaction time was confirmed by infrared spectroscopy at 2270 cm⁻¹. -1 The characteristic absorption peak of NCO completely disappeared, and the methyl ethyl ketone oxime blocked polyurethane prepolymer was finally obtained, hereinafter referred to as blocked prepolymer B.

[0037] Preparation Example 3: This preparation example provides a method for preparing a methyl ethyl ketone oxime-blocked polyurethane prepolymer, including the following steps: 105 parts by weight of poly(tetrahydrofuran) were added to a three-necked flask and the dehydration reaction was carried out at 115°C and a vacuum of -0.095 MPa for 2.5 h. Then the internal temperature of the three-necked flask was reduced to 42°C for later use. Maintaining a nitrogen protective atmosphere, 51.3 parts by weight of isoflurane diisocyanate were added to a three-necked flask, controlling the molar ratio of NCO groups to OH groups in the added substance to be 2.2. Then, the internal temperature of the three-necked flask was raised to 82°C, and the reaction was stirred at a constant temperature for 3.0 h. The mass fraction of free NCO groups in the mixture in the three-necked flask was measured to be 6.8%, and NCO-terminated polyurethane prepolymer was obtained. The internal temperature of the three-necked flask was lowered to 52°C, and 24.2 parts by weight of methyl ethyl ketone oxime was added dropwise at a uniform rate. The dropping rate was controlled, and the internal temperature of the three-necked flask was kept below 62°C. After the addition was complete, the mixture was kept at a constant temperature of 62°C in a sealed container for 2.5 hours. The reaction time was confirmed by infrared spectroscopy at 2270 cm⁻¹. -1 The characteristic absorption peak of NCO completely disappeared, and the methyl ethyl ketone oxime blocked polyurethane prepolymer was finally obtained, hereinafter referred to as blocked prepolymer C.

[0038] Preparation Example 4: This preparation example provides a method for preparing a temperature-responsive chelating catalytic switching complex, including the following steps: In a dry environment at 25°C, 1.0 parts by weight of dibutyltin dilaurate and 8.0 parts by weight of acetylacetone were added into a mixing container; The mixing vessel was started with the stirring function set to 350 rpm, and magnetic stirring was performed continuously for 20 minutes. Acetylacetone, in a molar excess relative to dibutyltin dilaurate, was used as the reaction solvent carrier to promote a complete coordination chelation reaction between the enol hydroxyl groups in acetylacetone and the tin metal center. Infrared spectroscopy confirmed that the characteristic carbonyl absorption peak of acetylacetone shifted to a lower frequency of 15 cm⁻¹. -1 Up to 25cm -1 The redshift indicates the formation of a stable liquid complex at room temperature. The liquid complex was then sealed and stored in the dark to obtain a temperature-responsive chelating catalytic switching complex, hereinafter referred to as catalytic complex A.

[0039] Preparation Example 5: This preparation example provides a method for preparing a temperature-responsive chelating catalytic switching complex, including the following steps: In a dry environment at 22°C, 1.2 parts by weight of dibutyltin dilaurate and 7.2 parts by weight of acetylacetone were added to a mixing container. The mixing vessel was started with the stirring function set to 300 rpm, and magnetic stirring was performed continuously for 15 minutes. Acetylacetone, in a molar excess relative to dibutyltin dilaurate, was used as the reaction solvent carrier to promote a complete coordination chelation reaction between the enol hydroxyl groups in acetylacetone and the tin metal center. Infrared spectroscopy confirmed that the characteristic carbonyl absorption peak of acetylacetone shifted to a lower frequency of 15 cm⁻¹. -1 Up to 25cm -1 The redshift indicates the formation of a stable liquid complex at room temperature. The liquid complex was then sealed and stored in the dark to obtain a temperature-responsive chelating catalytic switching complex, hereinafter referred to as catalytic complex B.

[0040] Preparation Example 6: This preparation example provides a method for preparing a temperature-responsive chelating catalytic switching complex, including the following steps: In a dry environment at 28°C, 0.9 parts by weight of dibutyltin dilaurate and 9.0 parts by weight of acetylacetone were added into a mixing container; The mixing vessel was started with the stirring function set to 400 rpm, and magnetic stirring was performed continuously for 30 minutes. Acetylacetone, in a molar excess relative to dibutyltin dilaurate, was used as the reaction solvent carrier to promote a complete coordination chelation reaction between the enol hydroxyl groups in acetylacetone and the tin metal center. Infrared spectroscopy confirmed that the characteristic carbonyl absorption peak of acetylacetone shifted to a lower frequency of 15 cm⁻¹. -1 Up to 25cm -1 The redshift indicates the formation of a stable liquid complex at room temperature. The liquid complex was then sealed and stored in the dark to obtain a temperature-responsive chelating catalytic switching complex, hereinafter referred to as catalytic complex C.

[0041] Example 1: This embodiment provides a flexible stone veneer processing technology, including the following steps: 100 parts by weight of the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, 15 parts by weight of resorcinol tetraphenyl diphosphate and 25 parts by weight of aluminum hydroxide were added into a high-speed disperser. The speed of the high-speed disperser was set to 1200 r / min and the mixture was stirred continuously for 16 min to obtain the base material mixture. Add 20 parts by weight of blocked prepolymer A, 35 parts by weight of polyetheramine and 1.5 parts by weight of catalytic complex A to the base mixture. Then, start the planetary mixer and set the speed to 400 r / min. Then, continue to degas and stir for 10 min under a vacuum of -0.09 MPa to finally obtain the reactive composite adhesive. Prepare a 3.0mm thick natural stone surface layer and clean its surface. Use a notched scraper to evenly apply the reactive composite adhesive to the back of the natural stone surface layer, controlling the application rate of the reactive composite adhesive to 800g / m². 2 Next, spread a layer of 160 g / m² on the surface of the reactive composite adhesive. 2 The fiberglass mesh layer is then repeatedly rolled with a pressure roller to ensure that the reactive composite adhesive completely penetrates the fiberglass mesh layer. A 1.0 mm thick fiberglass layer is covered on the surface of the fiberglass mesh. Then, the laminated board is sent into a hot press and the pressing pressure is set to 0.8 MPa. Next, the first stage curing process is carried out, and the temperature is kept constant at 40°C for 2.0 h. The conversion rate of primary amine in the system is confirmed to be greater than 98.2% by titration. This promotes the initial cross-linking of epoxy groups in the mixture with polyether amine to form the underlying skeleton and generate secondary hydroxyl groups. The second-stage curing process involved raising the hot press temperature to 80°C and maintaining it at that temperature and pressure for 3.0 hours. During this period, catalytic complex A responded to the heat change by releasing free tin metal centers. Simultaneously, under the efficient catalysis of these free tin metal centers, continuous monitoring using variable-temperature infrared spectroscopy confirmed that the system reached a 2270 cm⁻¹ temperature at 75°C. -1 The appearance of free isocyanate characteristic peaks at the point indicates that the closed prepolymer A is desealed and releases isocyanates. Subsequently, the isocyanates are grafted and crosslinked with the secondary hydroxyl groups produced in the first stage. Finally, after natural cooling to room temperature, a flexible stone finish is obtained.

[0042] Example 2: This embodiment provides a flexible stone veneer processing technology, including the following steps: 90 parts by weight of the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, 12 parts by weight of resorcinol tetraphenyl diphosphate and 20 parts by weight of aluminum hydroxide were added into a high-speed disperser. The speed of the high-speed disperser was set to 1000 r / min and the mixture was stirred continuously for 14 min to obtain the base mixture. Add 15 parts by weight of blocked prepolymer B, 30 parts by weight of polyetheramine and 1.2 parts by weight of catalytic complex B to the base mixture. Then, start the planetary mixer and set the speed to 350 r / min. Then, continue to degas and stir for 8 min under a vacuum of -0.085 MPa to finally obtain the reactive composite adhesive. Prepare a 3.5mm thick natural stone surface layer and clean its surface. Use a notched scraper to evenly apply the reactive composite adhesive to the back of the natural stone surface layer, controlling the application amount of the reactive composite adhesive to be 750g / m². 2Next, spread a layer of 150 g / m² on the surface of the reactive composite adhesive. 2 The fiberglass mesh layer is then repeatedly rolled with a pressure roller to ensure that the reactive composite adhesive completely penetrates the fiberglass mesh layer. A 0.8 mm thick fiberglass layer is covered on the surface of the fiberglass mesh. Then, the laminated board is sent into a hot press and the pressing pressure is set to 0.6 MPa. Next, the first stage curing process is carried out, and the temperature is kept constant at 35°C for 1.5 h. The conversion rate of primary amine in the system is confirmed to be greater than 97.6% by titration. This promotes the initial cross-linking of epoxy groups in the mixture with polyether amine to form the underlying skeleton and generate secondary hydroxyl groups. The second-stage curing process involved raising the hot press temperature to 75°C and maintaining it at that temperature for 2.5 hours. During this period, the catalytic complex B responded to the heat change by releasing free tin metal centers. Simultaneously, under the efficient catalysis of these free tin metal centers, continuous monitoring using variable-temperature infrared spectroscopy confirmed that the system reached a 2270 cm⁻¹ temperature at 72°C. -1 The appearance of free isocyanate characteristic peaks at the point indicates that the closed prepolymer B is desealed and releases isocyanates. Subsequently, the isocyanates are grafted and crosslinked with the secondary hydroxyl groups produced in the first stage. Finally, after natural cooling to room temperature, a flexible stone finish is obtained.

[0043] Example 3: This embodiment provides a flexible stone veneer processing technology, including the following steps: 110 parts by weight of the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, 17 parts by weight of resorcinol tetraphenyl diphosphate and 28 parts by weight of aluminum hydroxide were added into a high-speed disperser. The speed of the high-speed disperser was set to 1500 r / min and the mixture was stirred continuously for 20 min to obtain the base mixture. Add 25 parts by weight of blocked prepolymer C, 40 parts by weight of polyetheramine and 1.8 parts by weight of catalytic complex C to the base mixture. Then, start the planetary mixer and set the speed to 450 r / min. Then, continue to degas and stir for 12 min under a vacuum of -0.095 MPa to finally obtain the reactive composite adhesive. Prepare a 5.0mm thick natural stone surface layer and clean its surface. Use a notched scraper to evenly apply the reactive composite adhesive to the back of the natural stone surface layer, controlling the application amount of the reactive composite adhesive to be 850g / m². 2 Next, spread a layer of 170 g / m² on the surface of the reactive composite adhesive. 2 The fiberglass mesh layer is then repeatedly rolled with a pressure roller to ensure that the reactive composite adhesive completely penetrates the fiberglass mesh layer. A 1.2mm thick fiberglass layer was applied to the surface of the fiberglass mesh. The laminated sheet was then placed in a hot press with a pressing pressure of 0.9MPa. The first stage of curing was then performed, with the sheet held at 45°C for 2.5 hours. Titration confirmed that the primary amine conversion rate in the system was greater than 98.8%, which promoted the initial cross-linking of the epoxy groups in the mixture with the polyether amine to form the underlying framework and generate secondary hydroxyl groups. The second-stage curing process involved raising the hot press temperature to 85°C and maintaining it at that temperature for 4.0 hours. During this period, the catalytic complex C responded to the heat change by releasing free tin metal centers. Simultaneously, under the efficient catalysis of these free tin metal centers, continuous monitoring using variable-temperature infrared spectroscopy confirmed that the system reached a 2270 cm⁻¹ temperature at 78°C. -1 The appearance of free isocyanate characteristic peaks at the point indicates that the closed prepolymer C is desealed and releases isocyanates. Subsequently, the isocyanates are grafted and crosslinked with the secondary hydroxyl groups produced in the first stage. Finally, after natural cooling to room temperature, a flexible stone finish is obtained.

[0044] Example 4: This embodiment provides a flexible stone veneer processing technology, including the following steps: 95 parts by weight of the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, 18 parts by weight of resorcinol tetraphenyl diphosphate and 30 parts by weight of aluminum hydroxide were added into a high-speed disperser. The speed of the high-speed disperser was set to 1300 r / min and the mixture was stirred continuously for 18 min to obtain the base mixture. 22 parts by weight of blocked prepolymer A, 38 parts by weight of polyetheramine and 1.6 parts by weight of catalytic complex A were added to the base mixture. Then, the planetary mixer was started and the speed was set to 420 r / min. Then, the mixture was continuously degassed and stirred for 11 min under a vacuum of -0.088 MPa to finally obtain the reactive composite adhesive. Prepare a 4.0mm thick natural stone surface layer and clean its surface. Use a notched scraper to evenly apply the reactive composite adhesive to the back of the natural stone surface layer, controlling the application amount of the reactive composite adhesive to be 820g / m². 2 Next, a layer with a unit area mass of 165 g / m² is spread evenly on the surface of the reactive composite adhesive. 2 The fiberglass mesh layer is then repeatedly rolled with a pressure roller to ensure that the reactive composite adhesive completely penetrates the fiberglass mesh layer. A 1.1 mm thick fiberglass layer was applied to the surface of the fiberglass mesh. The laminated sheet was then placed in a hot press with a pressing pressure of 0.7 MPa. The first stage of curing was then performed, with the sheet held at 42°C for 2.2 hours. Titration confirmed that the primary amine conversion rate in the system was greater than 98.5%, which promoted the initial cross-linking of the epoxy groups in the mixture with the polyether amine to form the underlying framework and generate secondary hydroxyl groups. The second-stage curing process involved raising the hot press temperature to 82°C and maintaining it at that temperature for 3.2 hours. During this period, catalytic complex A responded to the heat change by releasing free tin metal centers. Simultaneously, under the efficient catalysis of these free tin metal centers, continuous monitoring with variable-temperature infrared spectroscopy confirmed that the system reached a 2270 cm⁻¹ temperature at 75°C. -1 The appearance of free isocyanate characteristic peaks at the point indicates that the closed prepolymer A is desealed and releases isocyanates. Subsequently, the isocyanates are grafted and crosslinked with the secondary hydroxyl groups produced in the first stage. Finally, after natural cooling to room temperature, a flexible stone finish is obtained.

[0045] Comparative Example 1: Compared with Example 1, the difference is that the blocked prepolymer A added to the base mixture is replaced with an equal weight of unblocked NCO-terminated polyurethane prepolymer without methyl ethyl ketone oxime blocking, and all other aspects are the same.

[0046] Comparative Example 2: Compared with Example 1, the difference is that the catalytic complex A added to the base mixture is replaced with 0.17 parts by weight of free dibutyltin dilaurate of the same effective component mass, and 1.33 parts by weight of acetylacetone is added to maintain the consistency of the solvent system, all other aspects are the same.

[0047] Comparative Example 3: Compared with Example 1, the difference is that the stepped temperature control steps of the first and second curing processes of the hot press are cancelled, and the curing process after being fed into the hot press is directly set to constant temperature and pressure holding at 80°C for 5.0 hours. All other aspects are the same.

[0048] Comparative Example 4: Compared with Example 1, the difference is that resorcinol tetraphenyl diphosphate was not added when preparing the base mixture, and the amount of aluminum hydroxide added was increased to 40 parts by weight, while the rest were the same.

[0049] Comparative Example 5: Compared with Example 1, the difference is that the polyetheramine added to the base mixture is replaced with ethylenediamine, a small molecule aliphatic curing agent with an equivalent amount of active hydrogen calculated according to stoichiometry; all other aspects are the same.

[0050] Test Example 1: Prepare the reactive composite adhesives obtained in Example 1, Comparative Example 1 and Comparative Example 2 as test samples. Place the prepared test samples in a vacuum constant temperature chamber at 40°C and perform static degassing treatment for 15 minutes under a negative pressure environment with a vacuum degree of -0.09MPa.

[0051] Start the rotary rheometer, install a parallel plate test fixture with a diameter of 25mm in the test module, set the detection gap between the upper and lower test plates to 1.0mm, and lock the temperature parameter of the rheometer test platform at a constant 40℃, and wait for the temperature probe parameter to stabilize.

[0052] Using a pipette, take 5 mL of the degassed reactive composite adhesive and apply it evenly to the center of the lower test plate of the rheometer. Lower the upper test clamp to the set 1.0 mm gap position and use a special metal scraper to scrape off the excess reactive composite adhesive that has overflowed under pressure along the edge of the test clamp.

[0053] Set a constant shear rate of 1 second in the equipment control software. -1 Start the dynamic time scan test program, set the continuous monitoring time interval to 0 min to 120 min, set the system to record the absolute viscosity value every 10 min, and at the same time turn on the device's built-in differential rheology module to calculate the viscosity evolution acceleration.

[0054] Record the initial viscosity values ​​of the system for each group of test samples at the corresponding time points, and simultaneously export the multi-dimensional data parameters required for the rheological state to cross the phase diagram. When the absolute viscosity parameter read by the testing instrument exceeds 300,000 mPa·s, the system automatically determines that the test substance has entered the gel solidification state and simultaneously terminates the data acquisition process of the current group.

[0055] For test samples that automatically trigger the power-off protection of the equipment due to the absolute viscosity of the system exceeding the upper limit of the testing instrument's range, the interruption is recorded as "Test terminated", and the viscosity value at the corresponding time point when the continuous monitoring procedure could not be completed is recorded as "-".

[0056] The test results are shown in Table 1.

[0057] Table 1. Viscosity evolution test data of Example 1, Comparative Example 1 and Comparative Example 2 under constant temperature of 40℃:

[0058] According to Table 1 and appendix Figure 1The data shows that the viscosity of Example 1 gradually increased from 842 mPa·s to 4157 mPa·s within a 120-minute test period. The absolute viscosity curve of Example 1 was flat and the viscosity evolution acceleration remained at a low level, indicating that the reactive composite adhesive did not produce a significant polymerization acceleration. The methyl ethyl ketone oxime blocked prepolymer and the free tin metal center locked by the coordination mechanism in the formulation maintained a chemically inert state in the 40°C environment. The inactive state of the two latent components blocked the large-area cross-linking of the polyurethane network. The reaction system relied only on the addition reaction between epoxy groups and polyetheramine, which was restricted by the steric hindrance of the long chain, to carry out network evolution. This caused the test sample to remain steadily in the primary fluid region throughout the monitoring period. The stable low viscosity state provided a flow window for the reactive composite adhesive to penetrate into the capillary pores of natural stone.

[0059] The comparative test results show that, using conventional NCO-terminated prepolymer, the viscosity of Comparative Example 1 suddenly increased to 89201 mPa·s after 30 minutes of testing. The absolute viscosity curve of Comparative Example 1 rapidly increased exponentially and the viscosity evolution acceleration increased sharply, proving that the highly active isocyanate groups that are not protected by the blockage directly undergo disordered urethane addition with polyetheramine at 40℃.

[0060] The test material was driven to leave the primary fluid region and rapidly cross to the viscoelastic transition region. Comparative Example 2 used uncoordinated dibutyltin dilaurate, which showed a high viscosity increase after 50 min of testing. The absolute viscosity curve of Comparative Example 2 showed a sudden inflection point in the second half of the test, accompanied by a significant amplification of the viscosity evolution acceleration, reflecting that the free metal catalyst exhibited catalytic efficiency at 40℃, which promoted the early coupling of molecular chain segments. As the uncontrolled crosslinking reaction continued, the test samples of Comparative Example 1 and Comparative Example 2 rapidly passed through the viscoelastic transition region and entered the gel-locking region. The dense three-dimensional network constructed inside the system restricted the sliding ability of the molecular chains, causing a complete loss of macroscopic fluidity and triggering equipment overload. The rheological differences proved that the introduction of a thermodynamically governed chemical shut-off switch and spatial chelation system into the reactive composite adhesive established a reaction sequence isolation barrier to prevent premature gelation in the primary stage.

[0061] Test Example 2: Prepare reactive composite adhesives for Examples 1, 2, and 3. Coat the reactive composite adhesives evenly on the surface of potassium bromide salt sheets, controlling the coating film thickness to be 0.05 mm, and obtain infrared spectroscopy test samples. In addition, inject the reactive composite adhesives of the corresponding group into a standard aluminum test crucible, controlling the sample mass to be 10.5 mg, and obtain thermal analysis test samples.

[0062] The infrared spectroscopy test samples from Examples 1 and 2 were placed on constant-temperature heating stages set at 40°C and 35°C, respectively, and subjected to constant-temperature treatment according to the time set in the first stage curing program of the corresponding group. After the treatment was completed, the infrared spectroscopy test samples were transferred into the sample chamber of the Fourier transform infrared spectrometer, and the infrared absorption spectrum at the end of the first stage was scanned and recorded. Subsequently, the infrared spectroscopy test samples were placed back on the constant-temperature heating stage, and the temperature was raised to 80°C and 75°C, respectively, according to the stepped curing program of the corresponding group. The temperature was then subjected to constant-temperature treatment according to the time set in the second stage curing program of the corresponding group, and the infrared absorption spectrum of the final cured product at the end of the second stage was recorded.

[0063] The infrared spectrum test sample of Comparative Example 3 was placed directly on a constant temperature heating stage set at 80℃ and kept at a constant temperature for 300 min. After the treatment was completed, the infrared spectrum test sample of Comparative Example 3 was transferred into the sample chamber of the Fourier transform infrared spectrometer, and the final infrared absorption spectrum of the single-stage high-temperature cured product was scanned and recorded.

[0064] The infrared absorption spectra acquired at each stage of the scan were baseline-calibrated using spectral analysis software, with a wavenumber of 3400 cm⁻¹ selected. -1 The characteristic broad peak of the secondary hydroxyl group nearby and the wavenumber of 3300 cm⁻¹ -1 The characteristic peaks of urethane bonds in the vicinity, and at 1600 cm⁻¹ -1 The absorption peak of the benzene ring skeleton vibration at the point is used as an internal standard peak. After the relative peak area is normalized, a regional integral operation is performed to extract the corresponding integral area value. Combined with the integral area value of the extracted urethane bond characteristic peak, the core operation variable is used. The dimensionless conversion is performed by the algorithm model built into the analysis software, and then the interfacial crosslinking coupling index used to characterize the internal chemical bonding density between the flexible polyurethane chain segment and the rigid epoxy network is derived.

[0065] After the thermal analysis test samples obtained in Examples 1, 2 and 3 were cured by step temperature control according to the first stage curing procedure and the second stage curing procedure of the corresponding group, they were placed in the heating furnace of the differential scanning calorimeter. High-purity nitrogen was introduced into the heating furnace as a test protective gas. The nitrogen flow rate was set to 50 mL / min, the initial temperature of the instrument was set to -50℃, and the temperature was continuously heated to 200℃ at a heating rate of 10℃ / min. Record the heat flow rate change curve within the heating range, extract the first glass transition temperature value corresponding to the baseline step in the low temperature region and the second glass transition temperature value corresponding to the baseline step in the high temperature region, and calculate the glass transition temperature difference between the two phases.

[0066] For test samples that did not undergo a stepped temperature-controlled segmented reaction cycle due to the use of a single-stage direct high-temperature curing process, the integral area value of the corresponding secondary hydroxyl characteristic peak at the end of the first stage, for which intermediate node sampling procedures were not performed, is recorded as "-".

[0067] The test results are shown in Table 2.

[0068] Table 2. Characterization parameters of microphase structure features of Examples 1, 2 and Comparative Example 3:

[0069] According to Table 2 and appendix Figure 2 The data shows that Example 1 exhibits significant retention of secondary hydroxyl groups in the final test of the first stage. The integral area of ​​the characteristic peak of secondary hydroxyl groups in Example 1 is 45.28. After the second stage of heating and curing treatment, the final cured product of Example 1 shows a higher integral area of ​​the characteristic peak of urethane bonds, with the value rising to 88.74. The glass transition temperature difference between the two phases of Example 1 is reduced to 19.45℃. The figure simultaneously reflects that the microphase evolution trajectory of Example 1 and the microphase evolution trajectory of Example 2 steadily cross the dashed line threshold and penetrate into the bottom micro-compatible region as the interfacial crosslinking coupling index increases.

[0070] The changes in test parameters indicate that the stepped temperature control process restricts the reactivity of isocyanate in the low-temperature range, prompting epoxy groups to preferentially open the ring and crosslink with polyetheramine to form a rigid underlying skeleton and reserve structural grafting sites. During the second stage of heating, isocyanate undergoes thermodynamic desealing and covalent addition reaction with the reserved secondary hydroxyl groups in the underlying skeleton. The rigid epoxy network and flexible polyurethane segments are connected by chemical bonds to form a forced interpenetrating polymer network structure, reducing the microscopic repulsion force of the original incompatible polymer phases and promoting compatibility shift between the two phases.

[0071] The comparative test results show that Comparative Example 3 uses single-stage direct high-temperature curing and lacks the formation period of preparatory grafting points. Table 2 shows that the integral area of ​​the characteristic peak of urethane bond in the final cured product of Comparative Example 3 is 21.53. The first glass transition temperature in the low-temperature region of Comparative Example 3 is -15.34℃ and the second glass transition temperature is far away at 112.57℃, with a glass transition temperature difference of 127.91℃ between the two phases.

[0072] Comparative Example 3 shows that the microphase evolution trajectory stagnates in the region of low interfacial crosslinking coupling index and extends towards the top macroscopic phase separation region. The relevant parameters and evolution trajectory indicate that in the direct high-temperature environment without phased temperature control isolation, the unsealed highly active isocyanate preferentially undergoes rapid polymerization with the free amine curing agent with low steric hindrance, and fails to establish effective covalent bond connection points with the epoxy ring-opening product. The two polymer network skeletons repel and separate at the macroscopic level, which hinders the construction of the forced interpenetrating polymer network structure. The experimental data prove that the two-stage temperature control sequence ensures molecular-level interface locking and inhibits phase separation between macromolecular chain segments.

[0073] Test Example 3: Prepare reactive composite adhesives for Examples 1, 3, 4, and Comparative Example 4. Inject each group of reactive composite adhesives into a standard polytetrafluoroethylene mold and cure them at a constant temperature according to the corresponding stepped temperature control program. Cut the cured material into limiting oxygen index test strips with dimensions of 130mm×6.5mm×3.2mm and vertical combustion test strips with dimensions of 125mm×13mm×3.2mm. Take internal debris from each group of cured material as thermal analysis test samples.

[0074] The limiting oxygen index (LOI) test specimen is vertically fixed inside the combustion chamber of the limiting oxygen index (LOI) measuring instrument. The ratio of oxygen to nitrogen mixed gas flow into the combustion chamber is adjusted. An ignition source is applied to the top of the LIO test specimen for combustion. The minimum oxygen volume percentage concentration required to maintain the LIO test specimen burning continuously for 3 minutes or to reach a burning length of 50 mm is recorded. The LIO value of the corresponding LIO test specimen is then extracted.

[0075] The vertical burning test specimen is held vertically in the vertical burning test chamber. A standard methane Bunsen burner is used to ignite the specimen at the bottom for 10 seconds, and then the flame is removed. The first flaming burning time of the vertical burning test specimen is recorded. After the flaming burning is extinguished, the flame is ignited again for 10 seconds and then removed. The second flaming burning time and the flameless incandescence time are recorded. At the same time, it is observed whether the degreased cotton at the bottom of the vertical burning test specimen is ignited by the burning drips. The vertical burning flame retardancy rating of the vertical burning test specimen is evaluated.

[0076] Weigh 8.5 mg of thermal analysis test sample and place it in the alumina crucible of the differential scanning calorimeter. Transfer the alumina crucible containing the thermal analysis test sample into the heating furnace of the thermogravimetric analyzer. Set the flow rate of the high-purity nitrogen protective gas to 50 mL / min and the initial test temperature to 30℃. Continuously heat to 800℃ at a heating rate of 10℃ / min.

[0077] Record the decrease in the mass percentage of the thermal analysis test sample as a function of heating temperature during the heating process, and simultaneously extract the rate of thermal weight loss (%·℃) of the system through differential calculation. -1 The data were extracted, along with the 5% thermogravimetric temperature value corresponding to a mass loss of 5% and the final char percentage value when heated to 800℃.

[0078] The test results are shown in Table 3.

[0079] Table 3. Test data on flame retardant performance and thermal stability of Examples 1, 3, 4 and Comparative Example 4:

[0080] According to Table 3 and appendix Figure 3 and attached Figure 4 The data shows that, with the increase of the flame retardant formulation addition gradient in Examples 1, 3, and 4, the limiting oxygen index increased from 28.6% to 34.3%, and the vertical combustion flame retardant rating remained at V-0. The 5% thermal weight loss temperature of Examples 1 to 4 shifted from 314.2℃ to 338.9℃, and the char rate at 800℃ increased from 21.6% to 32.5%. The main peak temperature of thermal degradation in the example groups shifted towards the high-temperature side with the increase of flame retardant formulation concentration, and the peak value of the maximum thermal weight loss rate correspondingly decreased. The evolution law of the test parameters shows that the liquid phosphate ester and aluminum hydroxide powder establish a gas-solid two-phase synergistic flame retardant network. In the initial stage of heating, the liquid phosphate ester decomposes and releases phosphorus-containing free radical groups into the gas phase space.

[0081] Phosphorus-containing free radicals capture active hydrogen and oxygen intermediates generated by the cracking of polyurethane epoxy resins, intervening in the chain combustion oxidation reaction in the gas phase region. Liquid phosphate esters at the condensed phase interface decompose into acidic polyphosphoric acid derivatives. The polyphosphoric acid derivatives act as dehydration catalysts to promote the dehydration, crosslinking, and char reconstruction of the polymer skeleton. Aluminum hydroxide powder decomposes upon heating, releasing water vapor to the interface to reduce the local oxygen concentration at the solid-liquid contact surface. The associated porous inorganic alumina skeleton is interspersed and retained inside the polymer char layer. The porous inorganic alumina skeleton crosslinks and intercalates with the polyphosphoric acid derivatives, solidifying in situ to form a dense phosphorus-aluminum hybrid heat-insulating char layer. The phosphorus-aluminum hybrid heat-insulating char layer slows down the heat and mass transfer process between the undecomposed polymer matrix and the external environment.

[0082] Comparative tests revealed that Comparative Example 4, which used only aluminum hydroxide powder for a high-filling process without adding liquid phosphate ester, showed a decrease in limiting oxygen index to 25.4%, vertical combustion flame retardancy rating to V-1, 5% thermal weight loss temperature to 296.7℃, and char residue at 800℃ to only 16.8%. Comparative Example 4 exhibited premature thermal degradation and a higher peak weight loss rate. The changes in test parameters proved that the single inorganic powder filling system lacked a gas-phase free radical capture mechanism and a condensed phase char-forming catalytic network. The aluminum hydroxide inorganic residue, lacking the cross-linking constraint of the polyphosphate network, was in a loose and free state, failing to interweave and form a continuous and tough carbon shell shielding layer on the surface of the reaction matrix. The high temperature and free oxygen in the external environment penetrated into the bottom matrix through the pores of the residue, causing severe thermal decomposition of the bottom matrix and deep continuous combustion. The experimental data confirmed that the liquid phosphate ester combined with solid aluminum hydroxide powder to construct a two-phase composite synergistic network improved the thermal environment stability and fire resistance of the reactive composite adhesive curing product.

[0083] Test Example 4: Prepare reactive composite adhesives for Examples 1, 2, 3, 3, and 5. Use the flexible stone veneers prepared in Examples 1, 2, 3, 3, and 5 as composite veneer test plates for subsequent physical performance testing. Cut the composite veneer test plates into 180-degree peel strength test strips with dimensions of 200mm × 25mm and flexural flexibility test strips with dimensions of 150mm × 50mm.

[0084] One end of the fiberglass layer of the 180° peel strength test specimen is fixed in the lower clamp of the universal tensile testing machine, and the other end of the ultra-thin natural stone veneer of the 180° peel strength test specimen is clamped in the upper clamp in the opposite direction. The tensile peel angle is set to 180 degrees, and the tensile running speed is set to 50 mm / min. The universal tensile testing machine is started to perform continuous peel tests, and the evolution curves of peel displacement and peel load strength are recorded simultaneously. The peel force value in the steady state stage during continuous peeling is recorded. Combined with the width parameter of the 180° peel strength test specimen, the value is calculated and extracted in N·mm. -1 180-degree peel strength data.

[0085] The bending flexibility test strip is placed on a bending tester with a standard cylindrical test shaft of gradient diameter, forcing the bending flexibility test strip to bend physically along the surface of the standard cylindrical test shaft until the bending angle reaches 180 degrees. A high-magnification magnifying glass is used to observe whether micro-cracks are generated on the surface of the ultra-thin natural stone veneer of the bending flexibility test strip, and at the same time, whether structural delamination occurs at the composite interface.

[0086] The bending test was repeated using standard cylindrical test shafts with decreasing diameters. The minimum cylindrical test shaft radius corresponding to the bending flexibility test spline maintaining structural integrity without fracture or delamination was recorded. The minimum cylindrical test shaft radius was extracted as the critical bending radius value. At the same time, the corresponding bending curvature data was obtained by taking the reciprocal of the cylindrical test shaft radius. The relative interface residual cohesion retention rate during the bending process was extracted and recorded simultaneously in conjunction with the interface mechanics monitoring system.

[0087] The test results are shown in Table 4.

[0088] Table 4. Comprehensive test data of interface mechanics and flexibility of Examples 1 to 3 and Comparative Examples 3 and 5:

[0089] According to Table 4 and appendix Figure 5 and attached Figure 6 The data shows that the 180-degree peel strength of Examples 1, 2, and 3 is 4.62 N·mm. -1 Up to 4.95 N·mm -1 The critical bending radius is 12.5 mm to 15.8 mm. After undergoing curvature bending, the ultra-thin natural stone veneer maintains structural continuity without surface cracking or interface delamination. The continuous physical deformation response process indicates that the long-chain polyetheramine component, in conjunction with the step-temperature controlled reaction program, promotes the toughening mechanism of the matrix crosslinking network.

[0090] The long-chain polyetheramine molecular skeleton is rich in flexible polyether segments. When the composite decorative test board is bent under stress, the flexible polyether segments absorb and dissipate the external mechanical deformation energy by absorbing and dissipating the work done by molecular segment rearrangement and stretching. The stepped temperature control process promotes the chemical intercalation of the bottom epoxy resin skeleton and the surface polyurethane flexible branches, generating covalent locking sites to strengthen the interfacial adhesion between layers. The covalent locking sites maintain the interfacial cohesion of the composite decorative test board under deformation conditions.

[0091] The 180-degree peel strength of Comparative Example 3 decreased to 1.24 N·mm. -1 The critical bending radius increased to 48.7 mm, and interfacial debonding and separation occurred during the bending process. Comparative Example 3 applied single-stage direct high-temperature curing parameters, blocking the sequential grafting crosslinking path between the epoxy underlayer network and the polyurethane surface network. The dissimilar macromolecular networks repelled and separated at the stress interface, resulting in the loss of cohesion at the composite interface and the inability to withstand the interfacial shear tensile force induced by bending deformation. Comparative Example 5 used a small-molecule rigid amine to replace the long-chain polyether amine, which had a strength of 3.87 N·mm. -1 With a peel strength of 180 degrees, the critical bending radius increases to 85.5 mm, triggering through-fracture of ultra-thin natural stone veneer during bending deformation.

[0092] Comparative Example 5 shows a sharp decline in residual cohesion at low bending curvature. The short-chain aliphatic amine structure increases the spatial cross-linking density of the underlying resin network and introduces rigid physical characteristics. The short-chain rigid cross-linking network lacks the ability of molecular chain segments to slip and displace under pressure, causing the adhesive substrate to lose its deformation energy dissipation characteristics. External bending stress cannot be buffered and absorbed by the underlying adhesive substrate, and the stress is directly transmitted and concentrated in the ultra-thin natural stone veneer layer, inducing structural brittle fracture. Mechanical data confirms that the polyetheramine long-chain structure combined with the stepwise cross-linking network framework can balance the high interfacial bonding strength and high bending flexibility of the reactive composite adhesive.

[0093] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to the equipment structure, process flow, step sequence, operating parameters, or working medium type in these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the core technical solutions disclosed above and their equivalent substitutions.

Claims

1. A flexible stone veneer processing technology, characterized in that, The process includes the following steps: The polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, resorcinol tetraphenyl diphosphate, and aluminum hydroxide were mixed and stirred to obtain a base mixture; Methyl ethyl ketone oxime blocked polyurethane prepolymer, polyetheramine and temperature-responsive chelating catalytic switching complex are added to the base mixture, and after degassing and stirring, a reactive composite adhesive is finally obtained. Prepare a natural stone surface layer, and evenly apply the reactive composite adhesive to the back of the natural stone surface layer; then lay a fiberglass mesh layer on the surface of the reactive composite adhesive, and roll it to make the reactive composite adhesive completely penetrate the fiberglass mesh layer; then cover the surface of the fiberglass mesh layer with a fiberglass layer, and send the laminated board into a hot press to apply pressure. The first stage of curing is carried out by heating and holding under pressure, which promotes the initial cross-linking of epoxy groups in the mixture with polyetheramine to form the underlying framework and generate secondary hydroxyl groups; The second stage of curing is carried out by continuing to heat up and maintaining constant temperature and pressure. The temperature-responsive chelate catalytic switching complex releases free tin metal centers in response to heat changes. Under the catalysis of the free tin metal centers, the methyl ethyl ketone oxime-blocked polyurethane prepolymer is deblocked and releases isocyanate. This causes the isocyanate to graft crosslink with the secondary hydroxyl groups generated in the first stage. After natural cooling, a flexible stone finish is obtained.

2. The flexible stone veneer processing technology according to claim 1, characterized in that, The step of mixing and stirring the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, resorcinol tetraphenyl diphosphate, and aluminum hydroxide to obtain the base mixture includes: 90 to 110 parts by weight of the polymer of 4,4'-(1-methylethylidene)bisphenol and (chloromethyl)ethylene oxide, 12 to 18 parts by weight of resorcinol tetraphenyl diphosphate, and 20 to 30 parts by weight of aluminum hydroxide are added to a high-speed disperser, the speed is set to 1000 to 1500 r / min and the mixture is stirred continuously for 14 to 20 min to obtain the base mixture.

3. The flexible stone veneer processing technology according to claim 1, characterized in that, The steps of adding methyl ethyl ketone oxime-blocked polyurethane prepolymer, polyetheramine, and temperature-responsive chelating catalytic switching complex to the base mixture, followed by degassing and stirring, to finally obtain a reactive composite adhesive include: After adding 15 to 25 parts by weight of methyl ethyl ketone oxime-blocked polyurethane prepolymer, 30 to 40 parts by weight of polyetheramine, and 1.2 to 1.8 parts by weight of temperature-responsive chelating catalytic switching complex to the base mixture, the planetary mixer is started and the speed is set to 350 r / min to 450 r / min. The mixture is continuously degassed and stirred for 8 to 12 minutes under a vacuum of -0.085 MPa to -0.095 MPa to finally obtain a reactive composite adhesive.

4. The flexible stone veneer processing technology according to claim 1, characterized in that, The step of preparing the natural stone surface layer and uniformly applying the reactive composite adhesive to the back of the natural stone surface layer includes: Prepare a natural stone surface layer with a thickness of 3.0 mm to 5.0 mm, and control the coating amount of the reactive composite adhesive to be 750 g / m². 2 Up to 850g / m 2 Apply the ointment; The step of laying a fiberglass mesh layer on the surface of the reactive composite adhesive includes: The mass per unit area of ​​the reactive composite adhesive liquid is 150 g / m². 2 Up to 170g / m 2 Fiberglass mesh layer; The steps of covering the surface of the fiberglass mesh layer with a fiberglass reinforced plastic (FRP) layer and then feeding the laminated sheet into a hot press to apply pressing pressure include: A fiberglass layer with a thickness of 0.8 mm to 1.2 mm is covered on the surface of the fiberglass mesh, and the laminated plate is sent into a hot press with a pressing pressure of 0.6 MPa to 0.9 MPa.

5. The flexible stone veneer processing technology according to claim 1, characterized in that, The step of heating and holding under pressure for the first stage of curing, which promotes the initial cross-linking of epoxy groups in the mixture with polyetheramine to form the underlying framework and generates secondary hydroxyl groups, includes: After being kept at a constant temperature and pressure of 35℃ to 45℃ for 1.5h to 2.5h, and after titration to confirm that the primary amine conversion rate in the system is greater than 97.6%, the epoxy groups in the mixture are initially cross-linked with the polyether amine to form the underlying framework, and secondary hydroxyl groups are generated.

6. The flexible stone veneer processing technology according to claim 1, characterized in that, Before the step of adding methyl ethyl ketone oxime-blocked polyurethane prepolymer, polyetheramine, and temperature-responsive chelating catalytic switching complex to the base mixture, followed by degassing and stirring to finally obtain the reactive composite adhesive, the step of preparing the methyl ethyl ketone oxime-blocked polyurethane prepolymer includes: Poly(tetrahydrofuran) was dehydrated under vacuum and then cooled for later use. While maintaining a nitrogen protective atmosphere, isoflurone diisocyanate was added, followed by heating and stirring at a constant temperature to obtain NCO-terminated polyurethane prepolymer. After cooling, methyl ethyl ketone oxime was added dropwise at a uniform rate, and the reaction was carried out in a closed environment at a constant temperature to obtain a methyl ethyl ketone oxime-blocked polyurethane prepolymer.

7. The flexible stone veneer processing technology according to claim 6, characterized in that, The step of dehydrating the poly(tetrahydrofuran) under vacuum conditions and then cooling it for later use includes: 95 to 105 parts by weight of poly(tetrahydrofuran) were subjected to a dehydration reaction at 105°C to 115°C and a vacuum of -0.085 MPa to -0.095 MPa for 1.5 to 2.5 hours, and then cooled for later use. The steps of maintaining a nitrogen protective atmosphere, adding isoflurane diisocyanate, and then heating and stirring at a constant temperature to obtain the NCO-terminated polyurethane prepolymer include: Maintaining a nitrogen protective atmosphere, add 38.0 to 51.3 parts by weight of isophorone diisocyanate, controlling the molar ratio of NCO groups in the isophorone diisocyanate to OH groups in the poly(tetrahydrofuran) to be 1.8 to 2.2, then raise the temperature to 75°C to 82°C, and stir the reaction at a constant temperature for 2.0 h to 3.0 h to obtain an NCO-terminated polyurethane prepolymer; The step of uniformly adding methyl ethyl ketone oxime after cooling and reacting in a sealed environment at a constant temperature includes: Cool the temperature to 48°C to 52°C, and add 13.9 to 24.2 parts by weight of methyl ethyl ketone oxime at a uniform rate, keeping the internal temperature below 62°C. After the addition is complete, keep the mixture at a constant temperature of 58°C to 62°C and allow it to react in a sealed environment for 1.5 to 2.5 hours.

8. The flexible stone veneer processing technology according to claim 1, characterized in that, Before the step of adding methyl ethyl ketone oxime-blocked polyurethane prepolymer, polyetheramine, and temperature-responsive chelating catalytic switching complex to the base mixture, followed by degassing and stirring to finally obtain the reactive composite adhesive, the step of preparing the temperature-responsive chelating catalytic switching complex includes: In a dry environment, dibutyltin dilaurate and acetylacetone are mixed and continuously stirred magnetically; By using acetylacetone as both a reaction solvent and a carrier, a coordination chelation reaction is initiated between the enol hydroxyl groups in acetylacetone and the tin metal center, thus obtaining a temperature-responsive chelate catalytic switching complex.

9. The flexible stone veneer processing technology according to claim 8, characterized in that, The step of mixing dibutyltin dilaurate and acetylacetone under dry conditions and continuously stirring magnetically includes: In a dry environment at 22°C to 28°C, dibutyltin dilaurate and acetylacetone were added to a mixing container at a mass ratio of 1:6-10, and the stirring speed was set to 300 r / min to 400 r / min. The mixture was then continuously stirred magnetically for 15 min to 30 min.

10. The flexible stone veneer processing technology according to claim 1, characterized in that, The second stage of curing, which involves continuing to heat and maintain a constant temperature and pressure, includes the following steps: the temperature-responsive chelate catalytic switching complex releases free tin metal centers in response to heat changes, and under the catalysis of these free tin metal centers, the methyl ethyl ketone oxime-blocked polyurethane prepolymer is deblocked and releases isocyanate. The temperature of the hot press is raised to 75°C to 85°C and held at a constant temperature for 2.5h to 4.0h. The temperature-responsive chelating catalytic switching complex releases free tin metal centers in response to heat changes. When the system reaches 72°C to 78°C, the methyl ethyl ketone oxime-blocked polyurethane prepolymer is triggered to deblock and release isocyanate.